Docência on-line: ser professor em cursos de turismo a distância - Arruda, Durcelina Ereni Pimenta (2016)
The context of this thesis involved the changes coming of digital technologies of information and communication and its implications for higher teaching tourism online. This work was located in the Knowledge and Educational Practices research line. The thesis defended was that the university professor working on degree courses online Tourism (distance) mobilizes knowledge and practices in implementing the face modality to modality of Distance Education (DE), setting each other and with the organization of their work reflections on the following categories of study: university teaching concepts; mediation; vocational training and teaching knowledge. Understanding the size of the pedagogical practices of teachers and the elements that move their practices in online teaching (or teaching in DE) involves understanding the tourism field and understand the growing phenomenon of distance education in different multidisciplinary fields in order to understand how teachers of different areas are involved and contribute to the formation of professional Tourism, by distance education mode. The theoretical references studied extended to the training of university teachers in Tourism and Distance Education, university teaching in a context mediated by digital technologies, the effects of technological change in pedagogical practices of the Tourism teacher and their knowledge and practices mobilized. The survey was conducted in two public institutions of higher education that offer the Degree in Tourism, from the response to the proposed electronic form. This was an exploratory analytical research, with quantitative and qualitative approaches. The research instrument used was built with closed questions (Likert scale, five points) and two open debate issues, which was presented to 60 teachers from the selected institutions, and obtained 10 responses to the questionnaires sent. The results show that teachers of undergraduate courses in Tourism engage and build specific knowledge for teaching online. The lack of systematization of this knowledge may be the major impediment to the design of an online teaching design, since it does not involve only digital technologies of information and communication, but also analog technologies. Teachers, in general, make reflections on their pedagogical, on the modality of distance education, about the difficulties of teaching and also to learn, and recognize its direct and indirect responsibility in this process.